(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines the trajectories of brand hate leading towards the consumer decision making process. Brand hate is an emotional state of the consumer wherein the intensity of consumers’ hatred and their self congruence could determine their actions towards the brand. 432 respondents spread across the main cities of Gujarat, India were administered a structured questionnaire. Principal axis factoring method along with Regression test were applied. Findings revealed a total accumulated variance of 59.943% for the four factors extracted using the PAF method. Four factors identified from the study were Simple brand hate, Negative personal experience, Negative brand image and Poor corporate social responsibility. The regression analysis revealed that respondents across age group, gender, income and occupation would not want to be consumers again of the brand that they hated. The second regression analysis indicated that respondent across age and gender had made financial sacrifice to not be consumers of the brand they hated. Brand and marketing managers need to closely understand and study these consumers who hate the brand because in today’s well connected competitive world, negativity about brands can spread like wild fire and damage control would be difficult if not impossible.